Engendering Playful Purpose in Pre-Service Early Childhood Educator Preparation: Why Community-Engaged Courses Matter - Cynthia A. Wiltshire; Robyn K. Pinilla; Heriberto J. Garcia (Education Sciences)
Play is often called the work of children, but questions abound about how early childhood educators are prepared to support children’s learning through play. In this study, we investigated undergraduate pre-service teachers’ perception of community-engaged coursework in the early childhood and elementary educator preparation program of a U.S.-based Hispanic-Serving Institution and how such a course could support student training and capacity for planning playful lessons. We analyzed data collected by our institutional Center for Community Engagement to understand the impact of field-based engagement on student experiences. Findings indicate that despite initially mixed perceptions, students developed professionally and felt positively about engaging children in various play types in the classroom. Practical implications for teacher educators and directions for future research are discussed.